BOARDING SCHOOL AND CHARACTER EDUCATION: EXPLORING MORAL DEVELOPMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS IN INDONESIA - Zainuri, Muhammad; Mu’alimin, Mu’alimin; Umam, Khotibul (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to explore how Islamic boarding schools (pesantren) in Indonesia play a strategic role in shaping students' character education amid the challenges of modernization and globalization. Employing a library research approach, this study critically analyzes primary and secondary literature from reputable journals to understand the development of moral values and character within Islamic educational institutions, particularly pesantren. The findings reveal that pesantren implement a holistic and integrated character education system based on exemplary behavior, habitual practices, and spiritual reinforcement. Pesantren have also demonstrated adaptability in responding to the demands of modern society without losing their traditional core values. The pesantren model, with its affective and transformative approach to character building, is deemed highly relevant for adoption in formal educational institutions as an alternative to current character education practices. These findings reinforce the argument that pesantren are not only historically relevant but also contextually and futuristically positioned to address contemporary moral and educational challenges. The study's main contribution is proposing a pesantren-based character education model as a pedagogical framework suitable for integration into the national education system.